Why do Women Use Midazolam in the Third Stage of Labor? An Exploratory Study - Abu Mahfouz, Ismaiel (Jordan Medical Journal, 2023)
Aims: The aims of this study were to report women’s reasons for using midazolam in the third stage of labor after the delivery of the fetal head, and report their knowledge of, attitudes toward, and satisfaction with its use. Methods and Materials: This prospective study was conducted between November 1, 2019 and November 1, 2020. Inclusion criteria were age 18 years or more, admitted into labor or for induction of labor, and having knowledge of midazolam. The women’s reasons, knowledge, attitudes, perceptions, and satisfaction were recorded and analyzed. Results: We recruited 200 women, mean age 29.4 years, 61% of whom knew about midazolam. Their reasons for choosing to have midazolam were relief of pain associated with the delivery of the fetal head, fear of delivery of the fetal head, and a desire to forget delivery details in 74%, 15%, and 11%, respectively. The factors that correlated positively with the women’s reasons for choosing midazolam included younger age, higher parity, and source of information due to being used in previous deliveries (all p-values were <0.05). Satisfaction was high in 88.5% of women. The factors that correlated positively with higher satisfaction included the women’s positive feeling about not recalling delivery details, and positive attitude toward the use of midazolam (all p-values were <0.05). Conclusion: The women chose to have midazolam for relief of pain associated with the delivery of the fetal head, fear of delivery of the fetal head, or a desire to forget delivery details. This reflects deficiencies in antenatal pain management counseling and the presence of barriers against the use of epidural analgesia.